Gender, Culture, and Social Media: Exploring Women’s Adoption of Social Media Entrepreneurship in Qatari Society - Hamda Al-Boinin; Savanid Vatanasakdakul; Wajdi Zaghouani (Administrative Sciences)
Purpose: Social media has become a significant catalyst for entrepreneurship in the Middle East, particularly for women. Considering the limited research conducted to understand the factors influencing social media adoption in conservative societies such as Qatar, this study aims to examine the factors affecting the adoption of social media among women entrepreneurs in Qatar and extend the Technology Acceptance Model (TAM) by including sociocultural variables. Method: The study employed a quantitative cross-sectional survey approach comprising 290 women entrepreneurs through an online survey. Structural Equation Modeling (SEM), particularly Partial Least Squares (PLS) analysis, was used to investigate relationships between constructs. Findings: The results highlight two dimensions that significantly affect women’s adoption of social media for entrepreneurship in Qatar: technological (perceived usefulness) and sociocultural (family influence, kinship roles, and reputation preservation). Through these factors, we found that women in Qatar are especially drawn to social media entrepreneurship because it enhances their business operations while being in line with their cultural and social values. Conclusion and Originality: This research is one of the pioneering studies on women entrepreneurship and social media in Qatar. It extends the technology adoption theory with novel sociocultural constructs specific for women entrepreneurship in the Middle East. This research offers insights that are significant for advancing the field of digital entrepreneurship and fostering women’s entrepreneurship and economic empowerment within Qatar and the other communities of the Middle East.